Evaluation of commercially available styrene-co-maleic acid polymers for the extraction of membrane proteins from spinach chloroplast thylakoids. (May 2019) - Korotych, Olena; Mondal, Jyotirmoy; Gattás-Asfura, Kerim M.; Hendricks, Jessica; Bruce, Barry D.
Graphical abstract: Highlights: Direct comparison of 12 commercial polymers for membrane protein (MP) extraction. Tested copolymers were both Na + and NH4 + salts of poly(styrene-co-maleic acid). The styrene-to-maleic acid molar ratio of the tested polymers ranged between 1 and 3. Only 5 polymers display high solubilization of chloroplast thylakoids. Top-5 polymers appear to yield similar qualitative results for MP extraction. Abstract: Solubilization of membrane proteins by poly(styrene-co-maleic acid) salts (pSMA-S) has significant potential for membrane protein studies. This approach provides an opportunity to overcome many disadvantages associated with a traditional detergent-based technique including protein denaturation and displacement of boundary lipids which may offer both structural and functional stability to membrane proteins. Thylakoid membranes (TMs) from photosynthetic organisms are well studied protein-rich membranes that host several multi-subunit protein complexes associated with oxygenic photosynthesis. These protein complexes are important for applied photosynthesis and by being extracted and purified they can be used in the near future for direct energy conversion. In this study, we used spinach TMs isolated from purified intact chloroplasts to systematically test the solubilization efficacy of 12 commercially available styrene-maleic acid (SMA) copolymers that vary in size, styrene-to-maleic acid molar ratio, and type of ester group. The efficacy of these pSMA-S to solubilize protein-containing biomembranes was evaluated via quantification of protein and chlorophyll content in the resulting SMA Lipid Particles (SMALPs). In addition, the extracted polymer-lipid-protein complexes were studied by low temperature fluorescence, sodium dodecyl sulfate and clear native polyacrylamide gel electrophoresis (SDS- and CN-PAGE), and immunoblot analysis. Our results indicate considerable variability in the solubilization efficacy of commercially available pSMA-S with at least 5 polymer formulations being able to efficiently extract membrane proteins from TMs. These 5 SMA copolymers may also be effective in extraction of membrane proteins from other biomembranes.